JENIS DAN PENGATURAN HAK KEKAYAAN INTELEKTUAL YANG DIAKUI DAN DILINDUNGI DI INDONESIA - Fachruddin Razi (Jurnal LEX SPECIALIS, 2010)
In the twenty one century the object of economic and trade not just only about goods and service, but it also include minds, ideas, creations, motions, arts and also knowledges, it also have been called the intellectual property rights, that rights is become very valuable because it containsmorality rights andof course  economic right, that the reason why the regulation that will protected that thing is also neededto give protection to the one who have been work hard for minds, ideas, creations, motions, arts and knowledges, not only that protection to the intellectual property rights it also will make investor come to this nation and it will make the economic tire round faster than before, shortly journal will explain about the basic regulation in protection of intellectual property rights in Republic of Indonesia. Key Note : Protection of intellectual property rights